(untitled) (Physical Education, Health and Social Sciences, 2025)
Green supply chain management, also referred to as sustainable supply chain management, is gaining more attention in organizations to meet sustainable goals while enhancing competitive advantage. In recent years, many companies have decided to adopt environmentally sustainable practices within their supply chain management processes. This article explores the relationship of GSCM with competitive advantage, operational efficiency, business sustainability and the moderating role of supply chain integration (SCI). This paper, therefore, used a quantitative research methodology. Data was gathered from 313 manufacturing companies in Indonesia operating in the electronics, agriculture, food and textile sectors. SEM was employed to examine the link between GSCM and competitive advantage drivers, including cost efficiency, innovation, product quality, delivery reliability, time to market, and firm performance. The findings also suggest that the GSCM relationship enhances operational efficiency and firm performance by lowering cost, improving resource utilization and impacting sustainability excellence. These factors create competitive advantages, such as cost and delivery reliability, and moderate the GSCM performance. Moreover, with SCI, these effects are further enhanced, especially the implications on the need for better supply chain integration of the various networks. GSCM brings benefits to firms in improving their performance and competitiveness; however, it is notable that this management system would encounter several barriers during its implementation, such as the high cost of implementation and resistance to change. To avoid short-term thinking and maximize all gains from GSCM, firms should implement investment in Digital SC solutions, train employees, and work closely with suppliers.